Financial Sector Performance: Evidence in Twelve West African Countries - Kamara, Ibrahim Sorie; Rahayu, Siti Aisyah Tri; Hakim, Lukman (Universitas Muhammadiyah Yogyakarta, 2020)
In most West African countries, the financial sectors are the least developed area. The absence of deep-efficient financial markets put major economic growth constraints. This study aimed to investigate the financial sector performance in twelve selected West African countries. To determine financial sector performance, a panel data semi-log model was employed. Data were collected from the World Bank Open data page from 2004-2013. The results revealed that both variables matched the hypothesis, indicating a positive impact in the financial sector. It indicated that the variables used in this study were major players of the financial sector in the selected countries. This study recommends that because financial stability, globally and within countries, generates jobs and improves productivity, more efforts should be made to ensure an effective and developed financial sector system. It is so because limited and inadequate access to credit will limit small and medium-sized enterprises' contributions to private sector development